Predicting The Locations of Caves and Rock Shelters in Western Part of Aceh Karst Using Geographic Information System - Setiawan, Taufiqurrahman; Nasution, Azhari Fitra (KALPATARU, 2023)
Geographic Information Systems (GIS) is a method used in archaeological research to provide information on landscapes and resources on the earth's surface and, combined with phenomena, predict the location of sites. This paper revealed some results of using this method in the case of karst in the western part of Aceh to find the locations of caves and inlets with GIS data sources. Satellite imagery, DEM, Topographic Maps, and Geological Maps, which overlayed with the geological structures, and the lithology of the location of the caves and inlets. The analysis results obtained that there were 26 areas grouped into five clusters of possible locations for caves and rock shelters.